2022
DOI: 10.35193/bseufbd.1167790
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacity Investigation for Some Markers Detecting Yellow Rust Resistance Genes in Bread Wheat Varieties

Abstract: Yellow rust is (Puccinia striiformis Westend. f. sp. tritici) is among the supreme diseases causing serious losses in wheat production. The chemical fungicides are commonly used in this disease-fighting. However, chemical control is not economical and also causes environmental pollution. Therefore, the use of resistant wheat varieties in production has critical importance. The resistance against yellow rust disease is expressed with Yr genes. In the breeding studies, knowing which parents include resistance ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A multitude of yield-related factors, such as plant height, the number of productive tillers, the number of grain spikes per spike, the weight of each spike, and thousand-grain mass, all have an impact on wheat production, a complex and polygenic trait.According to investigations, differences in the genotype of wheat cause changes in the number of spikelets on each spike. Furthermore, it was found that a plant's tiller count controlled the number of spikelets on each spike; plants with fewer tillers and spikelets per spike had larger seed weights because they were better at loading grains and absorbing nutrients [21]. The fertility of spikelets, or the number of kernels or spikelets, is one factor influencing the final grain yield.…”
Section: Influence Of Genotype On Wheat Yieldmentioning
confidence: 99%
“…A multitude of yield-related factors, such as plant height, the number of productive tillers, the number of grain spikes per spike, the weight of each spike, and thousand-grain mass, all have an impact on wheat production, a complex and polygenic trait.According to investigations, differences in the genotype of wheat cause changes in the number of spikelets on each spike. Furthermore, it was found that a plant's tiller count controlled the number of spikelets on each spike; plants with fewer tillers and spikelets per spike had larger seed weights because they were better at loading grains and absorbing nutrients [21]. The fertility of spikelets, or the number of kernels or spikelets, is one factor influencing the final grain yield.…”
Section: Influence Of Genotype On Wheat Yieldmentioning
confidence: 99%